Bioimpedance and impedance vector patterns as predictors of league level in male soccer players - Micheli, M. L.; Pagani, L.; Marella, M.; Gulisano, M.; Piccoli, A.; Angelini, F.; Burtscher, M.; Gatterer, H. (International Journal of Sports Physiology and Performance, 2014)
Purpose: Bioelectrical-impedance standards (resistance, reactance, and phase angle) are well established for the normal population or in the clinical setting and are considered indicators for cell mass, cell function, and hydration status. However, such standards do not exist for the male soccer population. Therefore, the goal of the current investigation was to provide a set of bioelectrical-impedance data of a large sample of soccer players with different performance levels. Methods: A sample of 893 players, registered in all Italian soccer divisions, was divided into 5 groups according to their performance level. Whole-body impedance measurements were performed during the first half of the competitive period. Besides estimation of body composition, bioelectrical-impedance vector analysis (BIVA) was performed. BIVA does not depend on equations and displays differences in hydration and body-cell mass (BCM). Individual vectors can be classified by using the 50%, 75%, and 95% tolerance ellipse. Results: In comparison with the other divisions and the normal population, the mean vector of the elite level showed a shift to the left (P < .001). Compared with the elite level, players of a lower performance level had lower phase angles, BCM, and fat-free mass. Conclusions: In conclusion, soccer players belong to a specific population. Muscle mass and function, as indicated by BCM and phase angle, increase with increasing performance level. The soccer-specific tolerance ellipses might be used for classifying individual vectors and to define target regions for low-level players.